ULAMA PEREMPUAN SEBAGAI MEDIATOR SAINS-AGAMA: KAJIAN FATWA DAN PANDANGAN TOKOH PEREMPUAN DALAM ISU KONTEMPORER ILMU FALAK - Naelul Marom (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2025)
The study of Ilmu Falak (Islamic Astronomy) in Indonesia is often dominated by male figures, both in determining religious law (fatwa) and its practice. This article analyzes the role of Women Scholars (Ulama Perempuan - UP) as a bridge (mediator) between the perspective of pure science (astronomy) and the view of Sharia (astronomical fiqh - fikih falak), particularly in contemporary issues such as the criteria for Hisab-Rukyat (calculation-sighting) and the Global Hijri Calendar. Using a descriptive qualitative method with content analysis of fatwas and the views of Indonesian female Falak figures (e.g., female Falak academics, members of the Lajnah Falakiyah - Astronomical Board), this study finds that Women Scholars tend to adopt an Integrative-Contextual approach. Women Scholars play a crucial role in reducing the tension of the Hisab-Rukyat conflict, positioning the consideration of social welfare (maslahat) (socio-astronomical aspects) alongside mathematical accuracy, and encouraging a gender equality perspective in the public space of Falak. The contributions of Women Scholars ensure that the Falak discourse remains relevant, moderate, and inclusive amid technological advancements and modernity.